A blueprinting approach to service innovation in private educational institutions - Youn Sung Kim; DonHee Lee; Ju hang Cha (International Journal of Quality Innovation, 2017)
This study proposes an efficient service delivery system using a blueprinting approach to service innovation in private educational institutions. This case study presents a flow chart based on administration blueprinting of a private preparatory school for college entrance examination, located in South Korea, to streamline process criteria based on administrative procedures for students and their parents. The results of the case study provide useful planning information for successful implementation of service blueprinting in private educational institutions. The study results are expected to help improve customer encounters as the service provider can employ effective processes. The study also sheds light on new operational management strategies for service innovation. By continuously improving information sharing, service encounters are expected to enhance customer satisfaction. The blueprinting technique can streamline the sequence of customer activities in a service process to meet customer expectations and needs. Thus, the approach could help researchers and administrators as certain how they might implement the system to correct failure points to successfully resolve difficulties.
Keywords: 650; Blueprinting approach; Service innovation; Educational institution; Customer satisfaction